Peran Guru Pendidikan Agama Islam Untuk Meningkatkan Karakter Sopan Santun Dalam Berbicara Siswa SMK 9 Medan - Hanifa Zahra; Kamil Kamil (Yayasan Rahmat Islamiyah, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in enhancing students' politeness in speech at SMK 9 Medan. This study employs a qualitative method with a descriptive approach, utilizing observation, interviews, and documentation for data collection. The findings indicate that students who receive PAI education better understand the importance of good communication and respecting others in speech. Additionally, the role of PAI teachers is significant in guiding and setting an example of polite communication practices.